Self-Concept of NPC Characters in the Video Game â€œA Space for the Unboundâ€ by Mojiken Studio [A Semiotic Analysis of Charles Sanders Pierce] - Kandiyastyanto, Muhamad Hakim Dwy Putra; Umam, Khothibul (Proceedings International Conference of Culture and Sustainable Development; Vol 2 (2024): PROCEEDINGS ICOCAS, 2024)
Modern literature has undergone significant transformations due to technological advancements and societal changes. Video games, as a form of new media, combine storytelling and interactive elements to create immersive experiences. This research examines how the concept of self is portrayed in the non-player characters (NPCs) of "A Space for the Unbound" using semiotic analysis based on Pierce's theory. The aim is to explore the fundamental elements of adventure video games in "A Space for the Unbound" and analyze the self-concept of NPCs using Carl Rogers' self-concept theory and Pierce's semiotics. This study emphasizes the potential of video games as a medium for literary and psychological exploration, contributing to the understanding of video games as complex, multi-dimensional literature. The qualitative study uses a descriptive- analytical approach, involving gameplay, observation, and documentation of interactions and narrative elements. Analysis is conducted using Theresa Dillon's basic game elements theory, Rogers' self-concept framework, and Pierce's semiotic model to interpret the game's visual and narrative signs. The game combines immersive storytelling with interactive gameplay, allowing players to explore deep emotional and psychological themes. NPCs are depicted with unique backgrounds and personalities. The "space dive" mechanic enables exploration of characters' inner thoughts and emotions, adding depth to the game experience. "A Space for the Unbound" demonstrates the potential of video games as a powerful medium for literary expression and psychological exploration. The study advances the field by applying semiotic and psychological theories to understand character development and narrative complexity in video games.
Keywords: Video Games, Semiotics, Self-Concept, Modern Literature, A Space for the Unbound